PENGARUH WORKING CAPITAL, TINGKAT SUKU BUNGA, INFLASI, & NILAI TUKAR RUPIAH TERHADAP IHSG PADA PERUSAHAAN SUBSEKTOR REAL ESTATE DAN PROPERTI DI BEI - Ambarwati; Dwi Puji Rahayu Dwi; Suwandi; Widya Tri Handayani Widya (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to determine the effect of macroeconomics on the Composite Stock Price Index so that investors get maximum profit with small risk when investing in the Indonesia Stock Exchange. The variables used in this study are working capital, interest rates, inflation, and the rupiah exchange rate. This study uses a quantitative approach. This study uses a period of quarter 1 2020 - quarter 1 2021. The sampling method used is purposive sampling and obtains a total sample of 19 companies. This study uses multiple linear regression analysis method performed with IBM SPSS version 26 which is supported by the classical assumption test. In addition, the F test, t test and coefficient of determination were carried out. Based on the results of the t test, working capital has a positive and significant effect on the JCI for the Real Estate & Property Sector, interest rates have a negative and significant effect on the JCI for the Real Estate & Property Sector, inflation has a positive and significant effect on the JCI in the Real Estate & Property Sector, and the value of The Rupiah exchange rate has a positive and insignificant effect on the JCI in the Real Estate & Property Sector. Keywords: Working Capital, Interest Rate, Inflation, Exchange Rate, Composite Stock Price Index